Ethnomathematics in Buna-Insana Motif Weaving Activity and its Link to School Mathematics - Aunga, Maria Marantika; Purwanto, Purwanto; Sukoriyanto, Sukoriyanto (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study explores ethnomathematics in the activity of weaving Buna-Insana motifs and its connection to school mathematics using an ethnographic case study with weavers from Botof Village, Insana District, guided by Bishop's ethnomathematics concepts: counting, measuring, designing, and reasoning. The results of the study indicate that the counting activity, mathematical knowledge in the form of addition operations is obtained. The measuring activity, hand spans are used as a unit of measurement. In the designing activity, the motifs produced are related to plane geometry concepts and similarity concepts. After the designing activity, reasoning activities are carried out. Implication logic is also found in weaving activities, namely when determining the selling price of woven fabrics and the length of weaving time.